Design of an air-duct pipe inspection and cleaning robot - Anuar A.; Md Saad J.; Arimi M.N.A. (Springer Science and Business Media Deutschland GmbH, 2023)
3D modeling; Air cleaners; Air conditioning; Ducts; Inspection; Machine design; Stress analysis; 3-D printing; Air ducts; Cleaning robot; Cool air; Fresh air; In-pipe robot; Inspection robots; Living environment; Pipe cleanings; Pipe inspection robot; Robots